My family: peekaboo (Brimax Scoresby, 2009)
"My Family" is a simple and engaging story that celebrates the diverse and loving dynamics of family life. It typically introduces different family members, such as parents, siblings, grandparents, and pets, highlighting their unique roles and relationships. Through relatable experiences and warm illustrations, the story emphasizes themes of love, support, and togetherness, encouraging children to appreciate their own families and the bonds they share.